O inglês como língua dos negócios : o caso da instrução comercial luso-brasileira (1759-1902) - Teles, Thadeu Vinícius Souza (2019)
This thesis investigates the history of English language teaching motivated by commercial reasons, in the context of the training of Portuguese and Brazilian traders, after the transfer of the Portuguese Court to Brazil, within the pedagogical aspect of Pombaline reformism. Thus, its time frame is located between the creation of the School of Commerce in 1759 and the end of the activity of the Commercial Institute of Rio de Janeiro in 1902. Its object is limited in the relationship between Luso-Brazilian commercial training and the process of constitution of English as main language for commercial purposes, preserved as a category of basic analysis the commercial education. Its main objective, in turn, is to analyze the configuration of English as a subject of teaching in commercial education, in Portugal and in Brazil. Through the evidentiary method, nineteenth-century legislation, compendiums and periodicals were grouped as sources for conducting the research. It was possible to conclude that the English language benefited from its application in everyday business and found in commercial education a fundamental factor for its dissemination in Lusitanian and Brazilian lands.